Kesabaran dan Academic Self-Efficacy pada Mahasiswa - Rizka Fitri Nugraheni (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2016)
The aim of this research was to find whether there's relationship between academic self-efficacy and shabr, as well as its supporting aspects. Participants were 108 undergraduate students. The instruments used were adapted version of College Questionnaire Academic Self-efficacy (Owen & Froman, 1988) and Shabr questionnaire (El Hafi, Rozi, & Mundzir, 2013). Data were analyzed with Pearson correlation. Results showed that there's significant correlation between shabr and academic self-efficacy. This finding can contribute to shabr theory construction and enhance comprehensive understanding about shabr among the community.Â Keywords: Academic self-efficacy, shabr, student